Design of a dynamic sonar emitter inspired by hipposiderid bats. (20th July 2018) - Yang, Luhui; Yu, Allison; Müller, Rolf
Abstract: The ultrasonic emission of the biosonar systems of bats, such as Old World leaf-nosed bats (family Hipposideridae) and the related horseshoe bats (family Rhinolophidae), is characterized by a unique dynamics where baffle shapes ('noseleaves') deform while diffracting the outgoing wave packets. As of now, nothing comparable to this dynamics has been used in any related engineering application (e.g. sonar or radar). Prior work with simple concave baffle shapes has demonstrated the impact of the dynamics on the emission characteristics, but it has remained unclear whether this was simply due to the change in aperture size or also influenced by the geometrical shape detail. Hence, it has also remained unclear whether it would be possible to further enhance the time-variant effects reported so far through different static and dynamic geometries. To address this issue, we have created a dynamic emission baffle with biomimetic shape detail modeled after Pratt's roundleaf bats ( Hipposideros pratti ). The impact of the dynamic deformation of the shape on the time-variant emission characteristics was evaluated by virtue of the gradient magnitude and the entropy in the gradient orientation. The results have shown that the dynamics results in much larger gradients in signal representation, which change jointly over direction and time.